Development of Case Based Learning Based E-Modules For Improving Junior High School Science Problem-Solving Skills - Setianingsih, Dina Ragilia; Ismawati, Riva; Rahayu, Rina (Phenomenon : Jurnal Pendidikan MIPA, 2024)
The 21st century requires students to have problem-solving skills as the ability to solve problems from previous activities to obtain new, more meaningful knowledge. PISA results in 2022 show Indonesia's science skills are low, especially in solving problems. The low problem solving ability is also experienced by SMPN 3 Mertoyudan students as evidenced by the analysis of ASAS 2023 results and interview results. The purpose of the research is to develop Case Based Learning-based e-modules that are valid, effective and practical to improve the KPM of junior high school students. This research method uses the Research and Development method with the ADDIE development model. The results of the research on the validity of the e-module showed an average assessment of 4.43 very valid with a feasibility percentage of 88.5% in the very feasible category. The effectiveness of e-modules based on the results of the t-test obtained sig 0.000, namely there is a significant difference and the magnitude of the increase in pretest and posttest results is high with a value of 0.70 in the N-Gain test. The practicality of e-modules is in the feasible category with a percentage of 81%. The conclusion of this study is that e-modules based on Case Based Learning are valid, effective and practical in improving problem solving skills. Suggestions from this study are expected to develop better e-modules with more complete, detailed material and clarity of instructions on e-modules.